Performance optimization of bijels as a novel type of catalyst support structure - Beunen, Johannes Martinus Peter; Harting, Jens (Materials Horizons, 2026)
Due to their high surface-to-volume ratio, porous media are very suitable catalyst support materials. However, the stochastic morphology of commercially available supports generally results in poor transport properties. Accordingly, the catalyst material contained in the support structures is used inefficiently. These issues can be alleviated by using catalyst supports acquired from spinodally-derived architectures due to their beneficial percolation properties. In particular, architectures derived from bicontinuous interfacially jammed emulsion gels (bijels) provide a viable route to the manufacture of stable catalyst supports that address the aforementioned issues. We investigate this type of porous support using a hybrid simulation method that combines a multicomponent lattice Boltzmann solver with the discrete element method. First, we simulate the formation of bijels and report on the improved properties of the resulting porous structures compared to stochastic equivalents for use in chemical reactors. Hereafter, we further validate the enhanced performance of bijel-derived geometries through miscible reactive flow simulations. Our findings suggest that bijel-derived catalyst support structures allow for an almost threefold increase in reactor effectiveness.
CRIS-Team Scopus Importer:2026-03-20